Uji Aktivitas Antibakteri Ekstrak Dan Fraksi Kulit Batang Dan Daun Sungkai (Peronema Canescens Jack) Terhadap Staphylococcus Aureus Atcc 25923 Dan Escherichia Coli ATCC 25922 - R. Herni Kusriani (Universitas Bhakti Kencana, 2015)
Sungkai (Peronema canescens Jack) is Indonesian indigenous plant, which has been used in traditional medicine as a mouthwash and minor injuries. This study aimed to determine the antibacterial activity of Sungkai bark and leaves and determined the active compounds as antibacterial. The sample was maserated with 96% ethanol as a solvent and fractionation was done by liquid-liquid extraction with n-hexane, ethyl acetate and methanol as solvents. Antibacterial activity assay was done by Broth Microdilution method and bioautography contact was done to determine the active compounds as antibacterial. The antibacterial activity test showed that Sungkai bark has no antibacterial activity against Staphylococcus aureus and Escherichia coli, while Sugkai leaves extracts, ethyl acetate fraction, and methanol fraction showed antibacterial activity against S. aureus with Minimum Inhibitory Concentration (MIC) Minimum Bactericidal Concentration respectively 1024 µg/ml, 1024 µg/ml dan 512 µg/ml and against E. coli with MIC and MBC of 512 ug/ ml.The result of bioautography test of Sungkai leaves extracts and fractions against S. aureus and E.coli showed that the predicted active antibacterial compounds were alkaloid and flavonoid. Conclusion : Methanol fraction of Sungkai leaves was the strongest antibacterial activity against S. aureus and E. coli bacteria with MIC and MBC value of 512 µg/ml